The evolution of care improves outcome in blunt thoracic aortic injury: A Western Trauma Association multicenter study. Issue 6 (December 2017) - Shackford, Steven R.; Dunne, Casey E.; Karmy-Jones, Riyad; Long, William; Teso, Desarom; Schreiber, Martin A.; Watson, Justin; Watson, Cheri; McIntyre, Robert C.; Ferrigno, Lisa; Shapiro, Mark L.; Southerland, Kevin; et al.
Abstract : BACKGROUND: The management of blunt thoracic aortic injury (BTAI) has evolved radically in the last decade with changes in the processes of care and the introduction of thoracic endovascular aortic repair (TEVAR). These changes have wrought improved outcome, but the direct effect of TEVAR on outcome remains in question as previous studies have lacked vigorous risk adjustment and long-term follow-up. To address these knowledge gaps, we compared the outcomes of TEVAR, open surgical repair, and nonoperative management for BTAI. METHODS: Eight verified trauma centers recruited from the Western Trauma Association Multicenter Study Group retrospectively studied all patients with BTAI admitted between January 1, 2006, and June 30, 2016. Data included demographics, comorbidities, admitting physiology, injury severity, in-hospital care, and outcome. RESULTS: We studied 316 patients with BTAI; 57 (18.0%) were in extremis and died before treatment. Of the 259 treated surgically, TEVAR was performed in 176 (68.0%), open in 28 (10.8%), hybrid in 4 (1.5%), and nonoperative in 51 (19.7%). Thoracic endovascular aortic repair and open repair groups had similar Injury Severity Scale score, chest Abbreviated Injury Scale score, Trauma and Injury Severity Score, and probability of survival, but differed in median age (open: 28 [interquartile range IQR, 19–51]; TEVAR: 46 [IQR, 28–60]; p < 0.007), zone of aortic injury ( p < 0.001), and grade of aortic injury (open: 6 [IQR, 4–6]; TEVAR: 2 [IQR, 2–4]; p < 0.001). The overall in-hospital mortality was 6.6% (TEVAR: 5.7%, open: 10.7%, nonoperative: 3.9%; p = 0.535). Of the 240 patients who survived to discharge, two died (one at 9 months and one at 8 years); both were managed with TEVAR, but the deaths were unrelated to the aortic procedure. Stent graft surveillance computed tomography scans were not obtained in 37.6%. CONCLUSIONS: The mortality of BTAI continues to decrease. Thoracic endovascular aortic repair, when anatomically suitable, should be the treatment of choice. Open repair remains necessary for more proximal injuries. Process improvement in computed tomography imaging in follow-up of TEVAR is warranted. LEVEL OF EVIDENCE: Therapeutic/care management, level III. Abstract : Supplemental digital content is available in the text.